ANALISIS PENERAPAN PERHITUNGAN DAN PELAPORAN BEBAN PAJAK PENGHASILANPASAL 21 PADA KARYAWAN TETAP PT MOPOLI RAYA MEDAN - Djong, Alexander Mario Retto; Situmorang, Dokman Marulitua; Indria, Dwihanna Santri (Journal Accounting International Mount Hope, 2023)
The purpose of this research is to find out the contitions of payment and income tax reporting to the permanent employees of PT Mopoli Raya Medan. Descriptive research approaches, and data sources obtained from primary and secondary methods. The results of the research concluded that the company is a legally resgistered taxpayer with proof of payment of PPH 21. The Company has a monthly and annual obligation ini making payments and tax reporting. All proved by the existence of transactions and proofs of payment and deposit and PPH 21 reporting carried out by the company. So it’s easier fot the company to get incentives from the government